(untitled) (Tempo e Argumento, 2013)
This article is about the publicization of self referential collections in a contemporary context of memorial search, in which are relevant Andreas Huyssen’s elaborations about "contemporary compulsion with memory" and François Hartog, around a change in " regime of historicity. Likewise, discusses the concept of self-production, through personal writings and archiving. Finally, we present the trajectories of launch and publicization of two self-referential documentary collections, letters of D. Joaquim, bishop of Pelotas, written between the years 1915 and 1940, Baroness Amelia’s letters, written between 1889 and 1918.